Direct numerical simulations of turbulent channel flows with mesh-refinement lattice Boltzmann methods on GPU cluster. (15th October 2020) - Wu, Chung-Ming; Zhou, You-Sheng; Lin, Chao-An
Abstract: Wall-bounded turbulent channel flows up to R e τ = 640 are simulated with multi-relaxation-time (MRT) lattice Boltzmann models. In order to perform direct numerical simulations and to resolve the wall boundary layer, a successive refinement procedure is developed to capture the rapid variation of the flow properties in the near-wall region. In the present implementation, three levels of grids are adopted with grid spacings in wall unit being Δ + ∼ 1, 2 and 4, respectively. Due to the explicit nature of the numerical scheme, the numerical procedure is built on the CUDA framework, and the simulations are conducted on the GPU cluster. Strong scaling shows satisfactory scalability of the present numerical procedure. Overall, for the present channel flows, simulated results ( R e τ = 180, 395, and 640) with D3Q19 and D3Q27 models show marginal differences. With the grid refinement, both models produce good mean and turbulent quantities compared with the benchmark solutions.